PEMANFAATAN LIMBAH SERBUK BATU MARMER DARI GUNUNG BATU NAITAPAN KABUPATEN TIMOR TENGAH SELATAN PADA CAMPURAN PAVING BLOCK - Hunggurami, Elia; Lauata, Meriyanti Flowrinda; Utomo, Sudiyo (Jurnal Teknik Sipil, 2013)
Mining of marble stone at Naitapan Stone Mountain waste floured marble sawn stone. Marble powder is a lot of buried material and its utilization is still relatively small. Seeing its potential, waste marble powder can be pursued for use as an alternative building material that is as fine aggregate substitute for sand in the manufacture of paving blocks. Replacement of sand with powdered marble will certainly affect the physical properties of the paving blocks, so that the study sought to find out great compressive strength and water absorption of aggregate paving block that uses finely powdered marble. Study the specimen in the form of paving block with dimensions of 20 x 10 x 6 cm by 60 test specimens treated with 2 marble powder replacement that is 50% and 100% of the weight of the sand and using a pressing of 50 kg/cm2 on comparative variation mixture of 1:2, 1:4, 1:6, 1:8 and 1:10. To determine the quality of paving block, then do the testing compressive strength and water absorption at 28 days old. Based on research results obtained that by pressing the same, paving block with a 100% replacement of marble powder produces compressive strength value is higher than the replacement of paving blocks with 50% marble powder. Water absorption of produced paving blocks with 100% replacement of marble powder is smaller than the replacement of 50% marble powder. Higher value of compressive strength of paving blocks at 28 days with 100% replacement of marble powder amounted to 39,75 MPa, 34 MPa, 25 MPa, 20 MPa and 14 MPa respectively each participated in the mixture ratio 1:2, 1:4 , 1:6, 1:8 and 1:10. With the higher water absorption value respectively also for each mixture ratio is equal to 7%, 7,45%, 7,48%, 7,51% and 7,59%. While the value of compressive strength of paving blocks with replacement of 50% marble powder amounted to 38,75 MPa, 25,50 MPa, 15 MPa, 11 MPa and 10 MPa respectively each participated in the mixture ratio 1:2, 1:4, 1:6, 1:8 and 1:10. And large water absorption value respectively also for each mixture ratio amounted to 8,15%, 8,88%, 9,09%, 9,29% and 9,31%.